Neurocognitive functioning in bipolar depression: a component structure analysis. Issue 5 (26th June 2013) - Gallagher, P.; Gray, J. M.; Watson, S.; Young, A. H.; Ferrier, I. N.
Abstract : Background: Previous studies of neurocognitive performance in bipolar disorder (BD) have focused predominantly on euthymia. In this study we aimed to compare the neurocognitive profile of BD patients when depressed with healthy controls and explore the component structure of neurocognitive processes in these populations. Method: Cognitive tests of attention and executive function, immediate memory, verbal and visuospatial learning and memory and psychomotor speed were administered to 53 patients with a SCID-verified diagnosis of BD depression and 47 healthy controls. Test performance was assessed in terms of statistical significance, effect size and percentile standing. Principal component analysis (PCA) was used to explore underlying cognitive factor structure. Results: Multivariate analysis revealed an overall group effect, depressed BD patients performing significantly worse than controls. Patients performed significantly worse on 18/26 measures examined, with large effect sizes (d > 0.8) on tests of speed of processing, verbal learning and specific executive/working memory processes. Almost all tests produced at least one outcome measure on which ∼25–50% of the BD sample performed at more than 1 standard deviation (s.d. ) below the control mean. Between 20% and 34% of patients performed at or below the fifth percentile of the control group in working memory, verbal learning and memory, and psychomotor/processing speed. PCA highlighted overall differences between groups, with fewer extracted components and less specificity in patients. Conclusions: Overall, neurocognitive test performance is significantly reduced in BD patients when depressed. The use of different methods of analysing cognitive performance is highlighted, along with the relationship between processes, indicating important directions for future research.